Abstract Braumann+Carlos+Filipe COMPSTAT 2008 - Braumann, Carlos A. (2009)
Oral communication at the international conference COMPSTAT 2008 (18th International Conference in Computational Statistics, Porto, August 2008). Web page: http://www.fep.up.pt/compstat08/ Stochastic differential equation models for the growth of populations and of individual animals in randomly fluctuating environments: extinction and persistence issues.